ANALISIS PERBANDINGAN ALGORITMA KRIPTO-GRAFI RSA DAN ElGAMAL UNTUK PENGAMANAN CITRA DIGITAL MEDIS COVID-19 - R. Irham Nurfi Satrio (2022)
Along with the development of technology, the need for safe and secure infor-mation exchange is also getting faster. With this information storage, a good secu-rity system is also needed to avoid crime and break-ins in the stored information. One form of securing existing information is to encrypt the data. There are many techniques and types of encryption, one of which is to use the RSA and ElGamal cryptographic algorithm methods. On the Open-Source Database on the Kaggle site, there is a collection of datasets that researchers can use to fulfill their research objectives, one of which is the MRI medical record images of patients affected by COVID-19. In this study, we will apply MRI medical image encryption using the RSA cryptographic algorithm and compare it with the ElGamal cryptographic al-gorithm to see the efficiency of the two algorithms seen from the encryption and decryption speed and the integrity of the digital image whether it changes or not. This research is expected to get benefits and outcomes in the form of considera-tion for digital image owners to use a more efficient algorithm method in this study and open insights regarding the efficiency of the implementation of both encryptions.